The mechanisms underlying altered somatoperception and somatosensation in healthy and subclinical populations - Perera, Andrea Treshi-Marie (2017)
Manipulating somatic representations has been found to alter somatic experiences; however, the precise mechanisms underlying these altered somatic experiences are as yet unclear. This thesis primarily investigated the mechanisms underlying altered somatic experiences following illusions that manipulated perception of the body representation. The current thesis also addressed individual differences in somatic perception across individuals with propensities towards various clinical conditions, including amplified somatosensory sensitivity and medically unexplained symptoms (MUS).